NEUROPROTECTIVE EFFECT OF AMORPHOPHALLUS CAMPANULATUS IN STZ INDUCED ALZHEIMER RAT MODEL - chen, Dong (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The present investigation deals with the assessment of neuroprotective effect Amorphophallus campanulatus (AC) tuber in alzheimer diseased (AD) rat and also postulates its possible mechanism of action. Material and Methods: AD was induced by administering streptozotocin i.e. STZ (3 mg/kg, ICV) day one and 3rd day after surgery. Surgery was performed on anesthetized rats by the help of stereotaxic apparatus. STZ induced AD rats were treated with petroleum ether extract of AC (100, 200 and 500 mg/kg, p.o.) for 14 days. Effect of AC tuber in AD rats were assessed by estimating the alteration in the behavior (Y maze apparatus and single trail passive avoidance), biochemical parameter in the brain tissue Oxidative stress parameters (SOD, CAT and LPO), amyloid β peptide (Aβ) and acetylcholinesterase (AchE) and histopathological study of brain tissue. Result: Treatment with AC shows significant (p<0.01) increased in the % of alteration in the behavior and step through latency in Y maze task and single trial passive avoidance test compared to AD rats. AC significantly (p<0.01) decreases the Aβ1-40, Aβ1-42 peptides and AchE in the brain tissue compared to AD rats. Whereas, treatment with AC significantly reduces the oxidative stress level in AD rats. Histopathological study reveals that treatment with AC extract reduces the amyloid plaque formation in the brain tissue of AD rat. Conclusion: The present study concludes the neuroprotective effect of AC extract in AD rats by reducing oxidative stress, Aβ and AchE in the brain tissue.